COLLEGE STUDENTS' VIEWS ON COMPLETING THE TEST THROUGH GAME-BASED LEARNING - Sitorus, Friska Ria; Silalahi, Wolter Parlindungan; Naibaho, Pestaria (Jurnal Bahasa Indonesia Prima (BIP), 2022)
Recently, game-based learning has been increasingly popular in education to increase the colleges' student participation in learning activities, especially conducting tests. This study examined the college students' learning experiences by conducting a pretest and posttest through the Kahoot application. This study recruited four college students aged twenty to twenty-two to participate who were selected purposely to provide "information-rich" cases. Focus group discussions were conducted to obtain rich information to solve the research question and analyzed through four steps: analyzing interview data, writing memos, creating the final report, and organizing the structure. The findings highlight three themes to describe such as (1) the implementation of game-based learning, (2) Students' challenges using Kahoot, and (3) The positive students learning outcomes of using Kahoot. The implementation of Kahoot can create a more attractive, exciting, and quality test atmosphere because students answer questions purely within a limited time setting. This activity also encourages students to repeat the previous material to think faster in submitting answers to the Kahoot!